Rediscovering the Islamic Classics : How Editors and Print Culture Transformed an Intellectual Tradition - El Shamsy, Ahmed (New Jersey Princeton University Press, 2020)
The story of how Arab editors of the late nineteenth and early twentieth centuries revolutionized Islamic literatureIslamic book culture dates back to late antiquity, when Muslim scholars began to write down their doctrines on parchment, papyrus, and paper and then to compose increasingly elaborate analyses of, and commentaries on, these ideas.
Include Bibliography and Index
Keywords: a